Quadri-stability of a spatially ambiguous auditory illusion - Bainbridge, Constance M.; Bainbridge, Wilma A.; Oliva, Aude (Frontiers in Human Neuroscience, 2015)
In addition to vision, audition plays an important role in sound localization in our world. One way we estimate the motion of an auditory object moving towards or away from us is from changes in volume intensity. However, the human auditory system has unequally distributed spatial resolution, including difficulty distinguishing sounds in front versus behind the listener. Here, we introduce a novel quadri-stable illusion, the Transverse-and-Bounce Auditory Illusion, which combines front-back confusion with changes in volume levels of a nonspatial sound to create ambiguous percepts of an object approaching and withdrawing from the listener. The sound can be perceived as traveling transversely from front to back or back to front, or “bouncing” to remain exclusively in front of or behind the observer. Here we demonstrate how human listeners experience this illusory phenomenon by comparing ambiguous and unambiguous stimuli for each of the four possible motion percepts. When asked to rate their confidence in perceiving each sound’s motion, participants reported equal confidence for the illusory and unambiguous stimuli. Participants perceived all four illusory motion percepts, and could not distinguish the illusion from the unambiguous stimuli. These results show that this illusion is effectively quadri-stable. In a second experiment, the illusory stimulus was looped continuously in headphones while participants identified its perceived path of motion to test properties of perceptual switching, locking, and biases. Participants were biased towards perceiving transverse compared to bouncing paths, and they became perceptually locked into alternating between front-to-back and back-to-front percepts, perhaps reflecting how auditory objects commonly move in the real world. This multi-stable auditory illusion opens opportunities for studying the perceptual, cognitive, and neural representation of objects in motion, as well as exploring multimodal perceptual awareness.